(untitled) (Archaeologia Adriatica, 2011)
During the excavations of a monumental structure (campus?) in the territory of Burnum Roman military camp, nine antefixa with a male tragic mask – with big and sad, realistically depicted eyes – stand out. they were unearthed in the layer which is characterized by shards of tegulae with the stamp of the VIII Legion. Their local production was possible after the end of 87 AD.